Code of conduct and ethics for civil servants in India and United Kingdom - Reddy, B. Ratan (1999)
With a brief introduction on evolution of civil servant's role in India, the author examines with concern the causes of civil servants' drifting away from rich traditional and classical values. Taking a closer look at the existing framework of ensuring proper conduct of civil servants in India (Constitutional provisions, anti-corruption laws, conduct rules, institutional arrangement therefor, etc.), he compares the Indian arrangement with that prevailing in the United Kingdom and works out his suggestions which, according to him, need to be implemented to set the things right. - Reproduced
Keywords: Civil service ethics - Great Britain; Civil service ethics - India; Civil service - Great Britain; Civil service - India; Civil service